Biodistribution of the radiopharmaceutical sodium pertechnetate after biliopancreatic bypass with a duodenal switch - Araújo-Filho,Irami (2007)
Study with the purpose to examine the effects of duodenal switch (DS), regularly performed in morbidly obese patients, on biodistribution of sodium pertechnetate in several organs of rats. There was no early or late mortality in either rats groups. The values of percent radioactivity per gram of tissue (%ATI/g), showed no significant difference in liver, stomach, small bowel, duodenum, kidney, heart, bladder, bone and brain, when compared the DS rats with sham and controls rats. A postoperative significant increase (p<0.05) in mean %ATI/g levels was observed in spleen, pancreas and muscle in group DS rats, as compared to group S and C rats. In the lung there was an increase and in thyroid a decrease in mean %ATI/g of DS rats, when compared to sham rats (p<0.05). In conclusion, the biliopancreatic diversion with duodenal switch in rats modified the biodistribution of sodium pertechnetate in thyroid, lung, pancreas, spleen and muscle.